2016
DOI: 10.5812/jjm.36582
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cytomegalovirus in Patients With Multiple Sclerosis: A Case-Control Study in Northern Iran

Abstract: BackgroundMultiple sclerosis (MS) is a chronic debilitating disease known as one of the most common neurological dysfunctions in young adults. Recent studies suggest that infections with herpesviruses play a critical role in the pathogenesis of MS.ObjectivesThe present investigation aimed to detect the presence of cytomegalovirus (CMV) in patients with MS using polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA) methods.Patients and MethodsPlasma and peripheral blood mononuclear cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In a case-control study in northern Iran, Najafi and colleagues found the DNA of CMV in 28% of patients with MS compared with only 2% in the control group. 31 Zivadinov and others reported a relationship between positive titer of CMV antibody and better clinical outcomes of MS, including a later onset of disease development in the lifetime, lower relapse of the disease, and less brain atrophy through MRI evaluation. 32 In contrast to Zivadinov and others, Salim and co-workers reported that CMV infection could intensify the clinical symptoms in patients with MS 32,33 , but our study suggests no association between a positive CMV infection and MS.…”
Section: Discussionmentioning
confidence: 98%
“…In a case-control study in northern Iran, Najafi and colleagues found the DNA of CMV in 28% of patients with MS compared with only 2% in the control group. 31 Zivadinov and others reported a relationship between positive titer of CMV antibody and better clinical outcomes of MS, including a later onset of disease development in the lifetime, lower relapse of the disease, and less brain atrophy through MRI evaluation. 32 In contrast to Zivadinov and others, Salim and co-workers reported that CMV infection could intensify the clinical symptoms in patients with MS 32,33 , but our study suggests no association between a positive CMV infection and MS.…”
Section: Discussionmentioning
confidence: 98%
“…The association of CMV and MS pathogenesis remains inconclusive. In two studies, higher loads of CMV DNA were demonstrated in an Iranian cohort of MS patients when compared to the controls [52,53]. Corroborating these data were findings that opportunistic reactivation of CMV infection can also occur in MS patients with this reactivation potentially exacerbating existing MS [54,55].…”
Section: Beta-herpesviruses (Cmv)mentioning
confidence: 97%
“…With regard to molecular evidence supporting a relationship between MS and HCMV infection, two different studies found higher HCMV DNA loads in a cohort of MS patients compared to HCs [ 202 , 203 ]. Moreover, the same authors detected positivity for anti-HCMV IgG antibodies in almost 80% of the MS patients examined.…”
Section: The Main Autoimmune Diseases Associated With Hcmv Infectimentioning
confidence: 99%